An investment plan for low-emission rice production in the Mekong River Delta region in support of Vietnam's Nationally Determined Contribution to the Paris Agreement - Tran, Van The; Mai, Van Trinh; Nguyen, Thi Dieu Trinh; Le, Hoang Anh; Richards, Meryl B.; Sebastian, Leocadio S.; Wollenberg, Eva Karoline; Vu, Duong Quynh; Sander, Björn Ole (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Rice production is integral to agriculture and food security in Vietnam, but it also contributes greenhouse gas emissions. In 2010, paddy rice production emitted 44.61 million tons carbon dioxide equivalents (MtCO2e), 18% of total national GHG emissions. A variety of options to mitigate GHG emissions from paddy rice show promise and will contribute to implementing Vietnam’s Nationally Determined Contribution (NDC) and green growth strategies. One of the most promising options is alternate wetting and drying (AWD), a technique in which fields are allowed to dry out to a certain point before irrigation instances. This paper focuses on the Mekong River Delta region, which produces more than 50% of total rice production and 95% of rice exported from Vietnam. This study employs a literature review, a study of promising GHG mitigation options, and an analysis of cost and benefits of AWD to develop an investment plan for AWD in the Mekong River Delta. In our field survey, we found AWD contributed to increasing farmers’ net incomes primarily by decreasing production costs. The study proposes an investment plan with four outputs and 15 investment activities with a goal of practicing AWD on 900,000 hectares in the Mekong River Delta and mitigating 10.97 M.tCO2e. A co-benefit is additional net income for farmers of 8,540 billion VND (USD 371.36 million) per year compared to conventional rice cultivation. The budget is USD 721.78 million (81.32% for hard infrastructure, 18.19% for MRV operation, research, performance and planning), of which 36.9% is provided by the state, 29.92% from local provinces, 21.77% from international support and 11.42% from the private sector. Mobilization of financial resources from public and private sectors and the integration into government plans and programs are recommended.